A study on the determinants of dividend payout ratio of Malaysian listed companies in oil and gas, consumer goods, and plantation sector / Zainal Amirul Aizad Zainal Arifen and Nur Zawani Yusof - Zainal Arifen, Zainal Amirul Aizad; Yusof, Nur Zawani (Faculty of Business and Management, 2016)
The purpose of this study is to find out the determinants of dividend payout ratio of companies listed in Bursa Malaysia from three different sectors which are consumer goods, oil and gas, and plantation sector. Dividends per share, leverage, and profit are the independent variables used for this study while the dependent variable is dividend payout ratio. There are three companies selected for every sector and the data spans from the year 2001 until 2015. Secondary Panel Data is applied for this study. Panel Regression Random Effect Model is employed to analyse the relationship between independent variables and dependent variable. It is found that dividend per share is positively correlated with the dividend payout ratio while leverage and profit are negatively related with dividend payout ratio respectively.